Digital and Spatial Studies of Religions - Hong, Z. George (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Digital and spatial studies of religions have developed rapidly as prominent research fields over the last two decades. This "spatial turn" has rippled through humanities and social sciences disciplines, and digital and spatial perspectives now occupy a central position in religious studies. However, various research efforts have led to disparate approaches to the digital and spatial study of religions without providing integrated and synergized connections between the digitalization and visualization of religious studies. This reprint aims to support and promote both digital and spatial studies of religions through interdisciplinary and multidisciplinary perspectives, including those of all historical periods, regions, and religions. Collectively, this reprint demonstrates that digital and spatial studies are unique and constructive ways of discovering, developing, and delivering religious studies that remain undiscovered or unaddressed through conventional research methodology. In an effort to supplement the current digital humanities in general, and the spatial study of religions in particular, the reprint presents theoretical or applied research papers on Chinese religious sites and mapping that are theory-driven, innovative, and data-based.